The views of commerce students regarding "free" higher education in South Arica - Bitzer, E.; De Jager, E. (South African Journal of Higher Education, 2020)
At the end of 2015, student protests (demanding ‘free’ higher education) took place at most South African universities. An official answer from the South African government regarding ‘free higher education’ is still being awaited. In the meantime, a zero present increase in university fees for 2016 and an increase of not more than 8% for 2017 was announced. South Africa is known for expensive higher education as tuition fees increase every year. Many students struggle to fund their studies, while government subsidies to higher education institution decrease. The question that remains is: Will it be feasible for South Africa to implement ‘free higher education’? This study aimed to investigate the perceptions of commerce students at one South African university regarding the feasibility of ‘free’ higher education. A questionnaire was used as research instrument which consisted of Likert-scale statements regarding general ideas about ‘free higher education’ as well as open-ended questions asking students about the definition of ‘free higher education’ and the effects on the South African economy. The results proposed that even though most students were aware of the students protests regarding ‘free higher education’ that took place, not all of them agreed with it. The respondents realised that it is not feasible for South Africa to implement ‘free higher education’ at this moment in time. Despite the views of these commerce students, if ‘free higher education’ were considered as a viable option in South Africa, implementation considerations should be examined. These issues will be discussed in a follow-up study.